Health implications of age and gender injury patterns of non-vehicle pedestrian trauma. (September 2021) - Rod, J.E.; King, Mark; Senserrick, Teresa; Oviedo-Trespalacios, Oscar
Abstract: Introduction: Walking is a healthy, environmentally sustainable, and economically profitable transportation strategy for citizens and governments. Despite these benefits, it is also important to understand, and to inform health professionals, policymakers, and public infrastructure planners about, the preventable injury potential of walking in the transportation system and the distribution of injury by gender and age. This is especially important for non-vehicle pedestrian trauma, given that is more prevalent and there is less information available about its injury outcomes in comparison to pedestrian injury caused by vehicle collisions. Method: A retrospective cohort study, and cross-sectional bivariate and multivariate analyses of non-vehicle pedestrian trauma in the traffic environment (NVPTE) were conducted. Relative risks (RR) of the incidence of injury and prevalence of injury outcomes by age and gender were calculated using data collected by the Queensland Injury Surveillance Unit (QISU) in Australia. Results: Pedestrians aged 60+ have a consistently higher risk of NVPTE incidence when compared with pedestrians aged <60. Older pedestrians have a higher risk of injury to the pelvis (RR 10.3 95% CI 3.81–27.5 p < 0.0001) and hip (RR 5.59 95% CI 3.53–8.85 p < 0.0001), and an adjusted higher risk of hospital admission (RR 1.5 95% CI 1.30–1.64 p < 0.0001). Pedestrian males <60 had more injuries to the head, sprains, strains and open wounds compared with females <60, while those aged 60+ had lower risk of fractures and higher risk of hospital admission. Conclusion: Promoting walking for transport requires the incorporation of prevention strategies that consider key differences in injury outcomes. Clinical fall risk assessments and protective pedestrian infrastructure could play an important role in reducing the health and economic burden of pedestrian falls to the health system. Highlights: Older pedestrians aged 60+ had higher risk of pelvis and hip fractures due to fall injuries. Among age and gender, there is variability in injury patterns. Increasing age is correlated with increasing hospital admissions. The incidence of older adults' non-vehicle pedestrian injury might be on an upward trend in Queensland Australia.